L2‐Betti numbers of totally disconnected groups and their approximation by Betti numbers of lattices. Issue 1 (28th February 2018) - Petersen, Henrik Densing; Sauer, Roman; Thom, Andreas
Abstract: The main result is a general approximation theorem for normalised Betti numbers for Farber sequences of lattices in totally disconnected groups. Further, we contribute to the general theory of L 2 ‐Betti numbers of totally disconnected groups and provide exact computations of the L 2 ‐Betti numbers of the Neretin group and Chevalley groups over the field of Laurent series over a finite field and their lattices.